VD_FINDINFO HC / 2015 / 465 vom 3. Juni 2015 - VD Tribunal cantonal (2015)
LIBERTÉ DE LA PRESSE, MÉDIA, PROTECTION DE LA PERSONNALITÉ, MESURE PRÉPROVISIONNELLE | 28 CC, 28a al. 1 CC, 28a al. 1 ch. 1 CC, 265 al. 2 CPC (CH)